2016
DOI: 10.1177/0020852315599047
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of empirical e-government research and its future research implications

Abstract: The desired e-government potentials and its shortcomings in reality are key reasons why e-government has become a major topic of interest to academics and practitioners, leading to an extensive body of knowledge. However, the literature still demands further quantitative empirical research to substantiate theory development. This situation calls for a specific review of the literature that arranges relevant knowledge and provides a solid foundation for future research. However, available meta-analyses do not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 41 publications
0
49
0
Order By: Relevance
“…This research area undoubtedly was, and still is, timely and fascinating: it is a well-known fact that the way the public sector relates to citizens has undergone a drastic transformation since the 1980s with the arrival of information and communication technologies (ICTs), and especially since the late 1990s with the advent of the Internet. Quantitative empirical e-government research still reflects a growing, open-ended field that provides many opportunities for investigation [9,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research area undoubtedly was, and still is, timely and fascinating: it is a well-known fact that the way the public sector relates to citizens has undergone a drastic transformation since the 1980s with the arrival of information and communication technologies (ICTs), and especially since the late 1990s with the advent of the Internet. Quantitative empirical e-government research still reflects a growing, open-ended field that provides many opportunities for investigation [9,15].…”
Section: Discussionmentioning
confidence: 99%
“…A growing corpus of literature has been analysing the impact of ICTs on the public sector from multiple perspectives, as reflected in extensive bibliographical reviews and meta-analyses covering definitions, scope, methods and recommendations (e.g., [8]), citizen orientation and adoption [9,10], stage models [11], diffusion [12,13], and the quality of these services [14]. The literature is flourishing, but [15] point out in their meta-analysis of empirical e-government research that in the literature there is still a shortage of authoritative quantitative empirical approaches and the topic is still perceived as a young field of research.…”
Section: Introductionmentioning
confidence: 99%
“…This research is a follow-up of the research done by Wirtz and Daizer (2016), which revealed that e-governance has become the main topic in both academic and practical research, which is expected to produce a body of knowledge in e-governance. They recommended quantitative research.…”
Section: Introductionmentioning
confidence: 90%
“…This might be why politicians and public administrators find it difficult to design and implement high-level ICT policies (Meijer, 2007). Although much focus in studies on technology-supported public services has been on qualitative explorations of the benefits and shortcomings of ICT use, Wirtz and Daiser (2018) note that there is still demand for rigorous quantitative empirical e-government research.…”
Section: The Impact Of Ict On Public Administrationmentioning
confidence: 99%
“…Governments are under pressure to increasingly render their services through competent application of ICT (Van Jaarsveldt and Wessels, 2015;Šiugždinienė et al, 2017). Despite growth in the number of studies evaluating the adoption, acceptance, performance, or success of national public administrations in general (see Wirtz and Daiser, 2016), the specific area of labour administration remains poorly understood (Hastings, 2016). As defined by Convention 150 of the International Labour Organization (ILO) -a United Nations agency developing labour standards, policies and programmes to promote decent work -labour administration refers to 'public administration activities in the field of national labour policies' (ILO, 1978).…”
Section: Introductionmentioning
confidence: 99%